My Colleagues Are My Friends: The Role of Facebook Contacts in Employee Identification. (August 2019) - Bartels, Jos; van Vuuren, Mark; Ouwerkerk, Jaap W.
This study examined the extent to which having colleagues as friends on Facebook influences departmental and organizational identification by blurring the boundaries between work and private life. Based on social identity theory and proxy efficacy, we argue that work-related friends on Facebook may affect employee identification with different levels of the organization. The results of an online panel study among Dutch employees (N = 1, 002) show that the perceived quality of online relationships with work-related Facebook contacts increases departmental identification, whereas the perceived authority of such contacts strengthens identification with the organization. Therefore, we suggest that blurring boundaries between work and private life through social media can have positive effects on organizational functioning.